Voxel-Based Lesion Analysis of Ideomotor Apraxia - Giovanna Oliveira Santos; Analía L. Arévalo; Timothy J. Herron; Brian C. Curran; Guilherme Lepski; Nina F. Dronkers; Juliana V. Baldo (Brain Sciences, 2024)
Ideomotor apraxia is a cognitive disorder most often resulting from acquired brain lesions (i.e., strokes or tumors). Neuroimaging and lesion studies have implicated several brain regions in praxis and apraxia, but most studies have described (sub)acute patients. This study aimed to extend previous research by analyzing data from 115 left hemisphere chronic stroke patients using the praxis subtest of the Western Aphasia Battery, which is divided into four action types: facial, upper limb, complex, and instrumental. Lesion–symptom mapping was used to identify brain regions most critically associated with difficulties in each of the four subtests. Complex and instrumental action deficits were associated with left precentral, postcentral, and superior parietal gyri (Brodmann areas 2, 3, 4, 5, and 6), while the facial and upper limb action deficits maps were restricted to left inferior, middle, and medial temporal gyri (Brodmann areas 20, 21, 22, and 48). We discuss ideas about neuroplasticity and cortical reorganization in chronic stroke and how different methodologies can reveal different aspects of lesion and recovery networks in apraxia.